ANALISIS MODEL PENGEMBANGAN KINERJA PEGAWAI PADA PUSKESMAS BALIK BUKIT LAMPUNG BARAT - Wenny Permata Sari; Restu Tria Wendra (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The Puskesmas is a community health service center, so it requires the performance of employees who carry out health service activities to the community to the maximum. One of the Puskesmas that always prioritizes the performance of its employees, namely the Balik Bukit Lampung West Health Center. The Balik Bukit Health Center is a community health service center that serves public health, especially in the West Lampung Regency area. The formulation of the problem in this study is how to model employee performance development and what are the supporting and inhibiting factors for the employee performance development model at the Balik Bukit Health Center, West Lampung Regency. The research approach used in this research is qualitative research with a descriptive approach. Collecting data using literature, observation, interviews and questionnaires. The research subjects in this study were 52 employees and used 4 informants, namely employees of the Balik Bukit Lampung West Health Center. Based on the results of the study it is known that the employee performance development model at the Balik Bukit Lampung West Health Center is carried out by knowing the quality, efficiency, discipline, initiative, thoroughness, leadership and honesty of employees when carrying out work activities. This employee performance development model will be able to influence the increase in employee performance at the Balik Bukit Lampung West Health Center. Supporting factors in the development of employee performance at the Balik Bukit Lampung West Health Center are conducive working conditions, both physical and non-physical work environments. There is compensation provided by management, work motivation in employees and there is career development in the Balik Bukit Lampung West Health Center. As for the inhibiting factors in the development of employee performance at the Balik Bukit Lampung West Health Center, namely the limited human resources at the Health Center, limited facilities and infrastructure. In addition, employee health is one of the obstacles to creating productive employees. For this reason, employees must maintain their health so that they can work productively so that they can support their performance